2009
DOI: 10.1073/pnas.0905906106
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of ADP-ribosylation removal revealed by the structure and ligand complexes of the dimanganese mono-ADP-ribosylhydrolase DraG

Abstract: ADP-ribosylation is a ubiquitous regulatory posttranslational modification involved in numerous key processes such as DNA repair, transcription, cell differentiation, apoptosis, and the pathogenic mechanism of certain bacterial toxins. Despite the importance of this reversible process, very little is known about the structure and mechanism of the hydrolases that catalyze removal of the ADP-ribose moiety. In the phototrophic bacterium Rhodospirillum rubrum, dinitrogenase reductase-activating glycohydrolase (Dra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(50 citation statements)
references
References 44 publications
(46 reference statements)
4
46
0
Order By: Relevance
“…ARH3 is structurally unrelated to PARG and is a member of the dinitrogenase reductase-activating glycohydrolase-related (DraG) protein family. DraG homologs in bacteria have been described as mono(ADP-ribosyl) hydrolases that control nitrogen fixation through protein de(ADP-ribosyl)ation (Berthold et al, 2009). ARH3, like other DraG proteins, possesses an all a-helical fold and relies on the presence of a conserved binuclear Mg 2+ cluster to assist the acid-base catalytic PAR degradation (Mueller-Dieckmann et al, 2006;Slade et al, 2011).…”
Section: Arh3mentioning
confidence: 99%
“…ARH3 is structurally unrelated to PARG and is a member of the dinitrogenase reductase-activating glycohydrolase-related (DraG) protein family. DraG homologs in bacteria have been described as mono(ADP-ribosyl) hydrolases that control nitrogen fixation through protein de(ADP-ribosyl)ation (Berthold et al, 2009). ARH3, like other DraG proteins, possesses an all a-helical fold and relies on the presence of a conserved binuclear Mg 2+ cluster to assist the acid-base catalytic PAR degradation (Mueller-Dieckmann et al, 2006;Slade et al, 2011).…”
Section: Arh3mentioning
confidence: 99%
“…In the most basic cases a single metal ion is coordinated by protein side chains, such as in the mononuclear non-heme iron enzymes [1]. Many proteins, however, utilize large and/or multiple metal clusters, such as iron-sulfur cluster proteins [2, 3], the nitrogenase system [47], and cytochrome c oxidase [8, 9]. They may also include other non-protein inorganic or organic molecules, such as the hydrogenases [10, 11] or heme [12, 13] and cobalamine proteins [14].…”
Section: Introductionmentioning
confidence: 99%
“…Alignment of the DraG and P II amino acid sequences (Fig. S4) and comparison of the A. brasilense (25) and R. rubrum DraG crystal structures (30) revealed that many contacts mapped in the A. brasilense GlnZ-DraG complex, are predicted to be conserved in the R. rubrum GlnJ-DraG complex (Table S1). In only a few cases there are changes in one or both proteins that could enable modified contacts.…”
Section: Comparison Of Glnz-drag Complex With the Putative Glnj-dragmentioning
confidence: 99%